Dissolved organic matter derived from aquatic plants in constructed wetlands: Characteristics and disinfection byproducts formation. Issue 3 (June 2022) - Pi, Jiachang; Zhu, Guangcan; Gong, Tingting; Lu, Yongze
Abstract: Constructed wetlands are used to improve water quality in the drinking water sources, but aquatic plants planted in constructed wetlands may be a source of disinfection by-product (DBP) precursors. This study explored the characteristics of aquatic plant-derived dissolved organic matter (DOM) and DBP formation in micro-polluted raw water treated by constructed wetlands. A simulated surface flow wetland (SSFW) planted with the typical aquatic plants Lythrum salicaria and Acorus calamus was studied. Raw water, control samples, effluent, and Suwannee River natural organic matter (SRNOM) were analyzed. via ultraviolet-visible (UV-Vis) spectroscopy, three-dimensional excitation emission matrix (3D-EEM) fluorescence combined with a parallel factor (PARAFAC) analysis, liquid chromatography-organic carbon detection (LC-OCD), principal component analysis (PCA), and other detection and analysis methods. A DBP formation potential (DBPFP) index was also constructed. Treatment by the SSFW increased the effluent dissolved organic carbon (DOC), UV254, trihalomethane formation potential (THMFP), haloacetic acid formation potential (HAAFP) by 72.2%, 171.4%, 83.7% and 88.6%, respectively. Planting aquatic plants in surface wetlands will negatively affect the water quality of micro-polluted raw water, with the plants being an important source of increased DBP precursors in wetland effluent. The effluent properties were similar to those of SRNOM, and had a higher degree of aromatization and larger molecular weight than raw water. The increased DBP precursors were mainly fulic acid and humus with higher aromatic and molecular weight, which derived from the growth and metabolism of aquatic plants. Humic substances (HS) accounted for the highest proportion of DOM in this study, with the average molecular weight of HS increasing from 648 to 698 g·mol −1 as the DOM content increased. Results from this study are particularly applicable to the establishment of constructed wetlands planted with aquatic plants in the drinking water sources, and the DOM derived from aquatic plants in constructed wetlands may be important precursors in the subsequent water disinfection process. Graphical Abstract: ga1 Highlights: Treatment by the wetland system increased the effluent THMFP and HAAFP significantly. DOM derived from aquatic plants in wetlands is an important precursor of disinfection by-products. The increased endogenous DBP precursors were mainly humic substances and fulvic acid.